"Probably the Most Beautiful Rowboat Afloat": The Form and Meaning of the St. Lawrence Skiff - Summers, John (Material Culture Review, 1998)
The St Lawrence skiff came to prominence as a regional watercraft type in the latter half of the nineteenth century. Skiffs were constructed and used on the American and Canadian sides of the St Lawrence River in the Thousand Islands region. While both American and Canadian skiffs shared most of the defining characteristics that made St Lawrence skiffs a recognizable watercraft type, there were also differences between skiffs built on either side of the river. This paper will consider the form and meaning of the skiff as both a watercraft type and a material culture object. A review of current notions of the ways in which artifact meaning is created, perceived and displayed sets up a discussion of the skiff’s multiple meanings and the contexts in which they occur. An analysis of the skiff’s categories of meaning shows how it evolved from a tool originally made locally by and for its users in a small-scale craft process to a fully realized consumer object and an icon of regional identity. The article concludes by considering how the meanings inherent in museum artifacts can be rehabilitated and relocated in living cultures. Résumé La yole du Saint-Laurent est parvenue au faîte de sa popularité en tant qu’embarcation régionale vers la deuxième moitié du XIXe siècle. La yole était construite et utilisée des côtés américain et canadien du fleuve, dans la région des Mille-Îles. Si les yoles américaines et canadiennes partageaient la plupart des caractéristiques de base qui démarquaient cette embarcation de toutes les autres, les yoles construites de part et d’autre du fleuve présentent des différences. Cet article examine la forme et la raison de la yole, tant à titre d’embarcation que comme objet de la culture matérielle. En passant en revue les notions actuelles relatives à la manière dont on crée, perçoit et illustre le sens d’un objet façonné, l’auteur ouvre le débat sur les nombreuses significations de la yole et leur contexte. L’analyse des différents sens de la yole montre comment cette dernière a évolué pour passer d’un outil au départ créé localement selon un procédé propre aux embarcations, parses utilisateurs et pour ceux-ci, à un véritable bien de consommation et emblème de l’identité régionale. L’article se termine en montrant comment on peut redonner aux objets conservés dans les musées leur sens inhérent et replacer celui-ci dans les cultures contemporaines.